THE ROLE OF LEADERSHIP, ORGANIZATIONAL COMMITMENT AND COMPETENCE IN THE ORGANIZATIONAL CULTURE OF THE STATE CIVIL APPARATUS AND ITS IMPLICATIONS FOR THE PERFORMANCE OF PUBLIC SERVICES IN THE TRADE AND INDUSTRY OFFICES OF REGENCIES - Syahrian (Dinasti International Journal of Management Science, 2020)
This research was conducted because West Java Province is a province with a large population when compared to other provinces in Java and still has limitations on efforts to improve the performance of public services in the trade and industry service district / city in West Java Province, where the performance of public services is still not good. This was allegedly due to the organizational culture of the state civil apparatus that did not meet the standards. The purpose of this study was to determine and examine the role of leadership, organizational commitment and competence in the organizational culture of the state civil apparatus and its implications for the performance of public services in the trade and industry offices of regencies / cities in West Java Province. This study uses SEM analysis tools with a number of samples, as many as 390 respondents. The sampling technique used is Proportional Stratistified Random Sampling. The results of the analysis obtained a significant influence both partially and simultaneously, from the Role of Leadership, Organizational Commitment and Competence to the organizational Culture of the Civil Service of the State, as well as a significant influence on the Work Culture of the State Civil Apparatus on the Performance of Public Services in the trade and industry services. district / city in West Java Province.